BETWEEN DIDACTICS, THE MENTOR AND THE PUPILS: TRAINEE REFLECTIONS CONCERNING THEIR TEACHING PRACTICES - Blaszk, Martin (Neofilolog, 2019)
Reflection in teacher development is important as it can help both experienced and novice teachers to better understand the processes they are involved in. It can also be used to aid evaluation processes. This paper presents a small scale study that involved undergraduate English philology students from Gdańsk University who were studying for the teacher specialisation. One of its purposes was to trial a strategy for feedback that could be used to mediate an already existing model of assessment for students’ taught lessons, which previous to the study used only a prescribed set of assessment criteria. Another purpose was to promote a reflective turn in both the student-teacher and academic mentor (myself), which would then inform the discussions that took place after each observed lesson. In addition to this, I was interested to find out if this strategy would generate a suitable quality and quantity of information, so that it might be used for further research. Overall, the strategy proved a useful aid to reflection in relation to the students’ teaching practices. As a research tool, it also generated usable data.